Experimental validation of a one-dimensional twin-entry radial turbine model under non-linear pulse conditions. (February 2021) - Serrano, Jose Ramon; Arnau, Francisco José; García-Cuevas, Luis Miguel; Soler, Pablo; Cheung, Raymond
This article presents the experimental validation of a complete integrated one-dimensional twin-scroll turbine model able to be used in reciprocating internal combustion engine unsteady simulations. A passenger car with a twin-entry-type turbine has been tested under engine-like pulse conditions by means of a specifically built gas stand. To obtain high-resolution quality data, the turbine and turbine line pipes have been instrumented with mean and instantaneous pressure sensors as well as temperature and mass flow sensors, employing a uniquely designed rotating valve for the pulse generation. This experimental configuration enables to obtain the pressure decomposition in both inlets and outlets of the turbine. Using the experimental data obtained, the model is fully validated, with special focus on the reflected and transmitted components for analysing the performance of the model and its non-linear acoustics prediction capabilities. The model presents a very high degree of correlation with the experimental results, providing a range of errors similar to the uncertainty of the measurements, even in the medium- and high-frequency spectra.